No effect of five days of bed rest or short‐term resistance exercise prehabilitation on markers of skeletal muscle mitochondrial content and dynamics in older adults. Issue 13 (3rd July 2022) - Marshall, Ryan N.; Smeuninx, Benoit; Seabright, Alex P.; Morgan, Paul T.; Atherton, Philip J.; Philp, Andrew; Breen, Leigh
Abstract: Bed rest (BR) results in significant impairments in skeletal muscle metabolism. Mitochondrial metabolism is reportedly highly sensitive to disuse, with dysregulated fission‐fusion events and impaired oxidative function previously reported. The effects of clinically relevant short‐term BR (≤5 days) on mitochondrial protein expression are presently unclear, as are the effects of exercise prehabilitation as a potential counteractive intervention. The present study examined the effects of a 5‐day period of BR and short‐term resistance exercise prehabilitation (ST‐REP) on mitochondrial‐protein content. Ten older men (71 ± 4 years) underwent 5 days of BR, completing four sessions of high‐volume unilateral resistance exercise prehabilitation over 7 days beforehand. Muscle biopsies were obtained from the vastus lateralis in the non‐exercised control and exercised legs, both pre‐ and post‐prehabilitation and pre‐ and post‐BR, to determine changes in citrate synthase enzyme activity and the expression of key proteins in the mitochondrial electron transport chain and molecular regulators of fission‐fusion dynamics, biosynthesis, and mitophagy. We observed no significant effect of either BR or ST‐REP on citrate synthase protein content, enzyme activity, or ETC complex I‐V protein content. Moreover, we observed no significant changes in markers of mitochondrial fission and fusion (p‐DRP1 S616, p‐DRP1 S637, p‐DRP1 S616/S637 ratio, p‐MFF S146, Mitofillin, OPA1, or MFN2 ( p  > 0.05 for all). Finally, we observed no differences in markers of biosynthesis (p‐AMPK T172, p‐ACC S79, PGC1 a, TFAM) or mitophagy‐related signaling (ULK‐1, BNIP3/NIX, LC3B I/II) ( p  > 0.05 for all). In contrast to previous longer‐term periods of musculoskeletal disuse (i.e., 7–14 days), a clinically relevant, 5‐day period of BR resulted in no significant perturbation in muscle mitochondrial protein signaling in healthy older adults, with no effect of ST‐REP in the week prior to BR. Accordingly, disuse‐induced muscle atrophy may precede alterations in mitochondrial content. Abstract : In contrast to previous longer‐term periods of musculoskeletal disuse, a clinically relevant 5‐day period of bed‐rest did not perturbate muscle mitochondrial protein signaling in healthy older adults. short‐term resistance exercise prehabilitation the week prior to bed‐rest also did not influence muscle mitochondrial signaling. Accordingly, disuse‐induced muscle atrophy may precede alterations in mitochondrial content.